Simulators in dentistry and clinical skill training: A permanent dialogue - Grandez Gomez, Kelly Estefany (2021)
Technological advance shows the great development of simulators in dental education. The use of simulators as an educational tool to achieve competencies in preclinical students has been increasingly incorporated into the study plans. Therefore, this article aims to review the history of simulators in dental education and identify the skills developed with the use of simulators in undergraduate university students worldwide. In this regard, a search was carried out for scientific articles indexed in databases such as Medline, Scopus, LILACS, SciELO, Academic Google and Redalyc; the bibliographic search was carried out until January 2021 and the following keywords were considered: simulation, dental education, dentistry students, competency-based education. In the results, four relevant stages were identified as an interactive way to explain the history of simulation in dentistry, each of these stages was determined due to the technological impact of each era, the need for training of the students and the integration into the study plans. It was concluded that there is evidence that the use of simulators during preclinical university training develops skills in dental students, these are related to the type of simulator used during their undergraduate training.